Clinical phenotype and mortality in patients with idiopathic small bowel villous atrophy: a dual-centre international study. Issue 8 (August 2020) - Schiepatti, Annalisa; Sanders, David S.; Aziz, Imran; De Silvestri, Annalisa; Goodwin, John; Key, Tim; Quaye, Lydia; Giuffrida, Paolo; Vanoli, Alessandro; Paulli, Marco; Cross, Simon S.; Vergani, Patricia; et al.
Abstract : Objective: Causes of small-bowel villous atrophy (VA) include coeliac disease (CD), its complications and other rare non-coeliac enteropathies. However, forms of VA of unknown aetiology may also exist. We defined them as idiopathic VA (IVA). To retrospectively classify the largest cohort of IVA patients and compare their natural history with CD. Methods: Notes of 76 IVA patients attending two tertiary centres between January 2000 and March 2019 were retrospectively reviewed. CD, its complications and all the known causes of VA were excluded in all of them. Persistence of VA during follow-up and lymphoproliferative features were used to retrospectively classify IVA, as follows. Group 1: IVA with spontaneous histological recovery (50 patients). Group 2: persistent IVA without lymphoproliferative features (14 patients). Group 3: persistent IVA with lymphoproliferative features (12 patients). Survival was compared between IVA groups and 1114 coeliac patients. HLA was compared between IVA patients, coeliac patients and appropriate controls. Results: Five-year survival was 96% in IVA group 1, 100% in IVA group 2, 27% in IVA group 3 and 97% in CD. On a multivariate analysis hypoalbuminemia ( P = 0.002) and age at diagnosis ( P = 0.04) predicted mortality in IVA. Group 2 showed association with HLA DQB1*0301 and DQB1*06. Conclusion: IVA consists of three groups of enteropathies with distinct clinical phenotypes and prognoses. Mortality in IVA is higher than in CD and mainly due to lymphoproliferative conditions necessitating more aggressive therapies.